1997
DOI: 10.1021/jf9607775
|View full text |Cite
|
Sign up to set email alerts
|

Reaction with Fructose Detoxifies Fumonisin B1 while Stimulating Liver-Associated Natural Killer Cell Activity in Rats

Abstract: Fumonisin B1 (FB1) was reacted with fructose in an attempt to detoxify this mycotoxin. Fischer 344/N rats were initiated with diethylnitrosamine (15 mg/kg body weight) and then fed 69.3 μmol FB1/kg diet or 69.3 μmol FB1 reacted with fructose (FB1−fructose)/kg diet for 4 weeks. In comparison with the rats fed basal diet or FB1−fructose, the FB1-fed rats had significantly increased plasma cholesterol (P < 0.01), plasma alanine aminotransferase activity (P < 0.05), and endogenous hepatic prostaglandin production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 38 publications
2
50
4
Order By: Relevance
“…DISCUSSION This study demonstrated that subjecting FB 1 to a nonenzymatic browning reaction with glucose avoided FB 1 toxicity as reflected in plasma total cholesterol concentration, ALT activity, development of GGT-and PGST-positive AHF, concentration of endogenous hepatic PGE 2 , accumulation of Sa, or the Sa/So ratio. These results agreed with the findings of Lu et al (13) in which FB 1 was detoxified by reaction with fructose. Because the FB 1 -fructose and FB 1 -glucose products are likely to be similar, both reactions probably had similar detoxification effects.…”
Section: Effect On Body Weight Gains Relative Liversupporting
confidence: 93%
See 1 more Smart Citation
“…DISCUSSION This study demonstrated that subjecting FB 1 to a nonenzymatic browning reaction with glucose avoided FB 1 toxicity as reflected in plasma total cholesterol concentration, ALT activity, development of GGT-and PGST-positive AHF, concentration of endogenous hepatic PGE 2 , accumulation of Sa, or the Sa/So ratio. These results agreed with the findings of Lu et al (13) in which FB 1 was detoxified by reaction with fructose. Because the FB 1 -fructose and FB 1 -glucose products are likely to be similar, both reactions probably had similar detoxification effects.…”
Section: Effect On Body Weight Gains Relative Liversupporting
confidence: 93%
“…Greater hepatic prostaglandin F 2R production was also observed in FB 1 tumor promotion in rat liver (13). In vivo administration of 50 ppm of FB 1 significantly suppressed hepatic natural killer (NK) cell activity while stimulating hepatic preneoplasia (13). NK cell activity suppression by FB 1 during tumor promotion may be mechanistically significant, but this remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (28) reported that treatment of FB 1 with fructose under these conditions resulted in a significant reduction in detectable FB 1 . More importantly, when a diet containing the product of the FB 1 -fructose reaction was fed to rats, it was not toxic and did not result in cancer initiation (28). Another reaction that has been investigated is the treatment of maize with a combination of H 2 O 2 and NaHCO 3 .…”
Section: Developing Methods For Reducing Fumonisinsmentioning
confidence: 98%
“…AFs levels can be reduced by up to 92% during the preparation of the Mexican drink "atole" by heating at 94°C for 10 minutes and then drying at 40°C for 48 hours. In the production of corn flakes the AFs level is reduced by heating up to 64%, while after roasting, both with and without added sugar, the reduction is 78-85%, respectively [27]. Extrusion is a process frequently used to produce breakfast cereals and snacks: in this case temperature higher than 150°C can reduce AFB1 contamination of 50-80%, while the addition of 0.7% ammonia, 1% hydroxide or 0.4% bicarbonate allows to reach a reduction up to 95% [28].…”
Section: Aflatoxinsmentioning
confidence: 99%
“…The extrusion grits cooking caused significant reduction of FB1 in all treatments if compared with the not extruded used as control. The use of glucose resulted in a greater reduction (44.8-66.6%) compared to fructose (32.4-52.2%) or sucrose (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).7%) use.…”
Section: Fumonisinsmentioning
confidence: 99%